Amazonian historical ecologies - Rival, L (Wiley-Blackwell, 2006)
Historical ecology may be defined as the undertaking of a diachronic analysis of living ecological systems, with the view to accounting more fully for their structural and functional properties. Historical ecology, more an approach or a research strategy than a paradigm, addresses a central question: 'How does environmental change relate to the historical development of human societies?' An integral part of the new ecological anthropology, historical ecology seeks to dereify the concepts of nature and culture, and to rethink critically the complexity of the biological world, particularly the problematic distinction between the wild and the domesticated, which has hitherto inspired natural science research on the diversity of biological life. This paper examines the ways in which historical ecology has been used to research nomadic bands subsisting with few or no domesticates in lowland South America. I argue that current knowledge of the Amazon biome, which is far more sophisticated than it was in the late 1940s and early 1950s, when Steward edited the Handbook of South American Indians, allows us to rethink human occupation of, and adaptation to, the Amazon; to redefine the forces that have shaped the material dimensions of social life, and to recognize that Amazonian hunter-gatherers have played an active part in the making of the natural environment that they have occupied for millenia. I also argue that 'trekking', far from representing a necessary intermediary stage in the regression from horticulture to foraging, constitutes, in some cases, a sui generis solution to deep contradictory forces of a political, religious, and social character. Such internal processes may have long predated the Conquest and the disruptions it caused. I conclude that reliance on resources created in the past may be a characteristic shared by various trekking and foraging groups of the Upper Amazon.